Пафос життєствердження в новелі Степана Васнльченка "На калиновім мості" - Антоненко, А. (Літературознавчі обрії. Праці молодих учених, 2010)
In the article, devoted to Stepan Vasylchenko’s creative work, whose prose is by itself the synthesis of typical signs of both European and Ukrainian variants of the modernistic aesthetics, the short story «On the snowball tree bridge» is analyzed. The life-asserting pathos of liberation of a man sounds in every line of the short story «On the Snowball Tree Bridge». Its characters look for the ways of liberation for themselves and other people and find them loyal to the ideals of revolution, love, their moral-ethic convictions.